Rekonstruksi Hukum Kewarisan Beda Agama Ditinjau dari Al-Ushūl Al-Khamsah (Mazahib, 2017)
Islamic Inheritance Law is believed to be a law containing rules that are in line with public interest. Hence, only few Moslem scholars (ulama’) have conducted ijtihad on the topic in order to reform its rules and bring them pursuant to contemporary situation. Consequently, when there is a gap between the ideal of Islamic inheritance law (i.e. maslaha) and its application in the Islamic society, a rational ruling over the problem of inheritance division faced by Moslems becomes unavailable. Given this, it is necessary to re-interprete the textual sources of Islamic Inheritance Law, in order to come up new rules pursuant to the objective of syari’ah. One of the pressing problems need to be resolved is about the status of Muslim heirs whose inherits from their non-Moslem family. This article thus discusses two main issues: first, what the opinions of Moslems scholars are about a Moslem who inherits from his/her non-Moslem family; and second, which opinion is the most relevant to the al-uṣhūl al-khamsah. This article is doctrinal legal research which employs comparative and deductive analysis. It reveals that: (1) the Moslem scholars are devided into two groups of thought, the first group forbid a Moslem to inherit from his/her non-Moslem family, and the second group allow it; (2) the most relevant opinion to the objective of syari`ah is the second opinion. This is so because the admissibility of a Moslem to inherit from his/her non-Moslem fulfils the criteria of public interest of essential and complimentary level. Keywords: Islamic Inheritance law, interfaith inheritance law, istiṣlāhi, al-uṣūl al-khamsah.